An interpretation of values and comprehension of ideał of morał right - Nikiel, Tania (Studia Psychologica: Theoria et praxis, 2009)
Detecting the ideal of moral good, to which essence the man is appealing at choice the most appropriate conduct for its development, is underestimated in contemporary psychological theories. The ideal of moral good is closely connected with understanding values, which are being investigated from different perspectives in the humanities. Contextual character of performing (functioning) of moral values was emphasized which are reference to particular conceptualisation the right ideal of the moral good. The paper also focuses on the role of interpretation until the ideal of moral good will be perceived for bringing values into effect.